Workplace bullying, psychological distress, and work engagement in the hospitality industry: The moderating effect of self- compassion - Anasori, Elham; Soliman, Mohammad; Costa, Carlos (Varna Univ Management-Vum, 2023)
The present study investigates the structural associations between workplace bullying, employee psychological distress, and work engagement within the hospitality setting. It also evaluates the moderating impact of self -compassion on the direct path between workplace bullying and employee psychological distress. Employing a quantitative approach, PLS-SEM has been applied to analyse the data, collected by survey, from full-time employees at 2-star and 3-star hotels in Antalya. The results indicated that workplace bullying significantly predicted psychological distress and deteriorated employee engagement. In addition, there is a significant effect of employees' psychological distress on their engagement. However, employee self-compassion did not significantly moderate the effect of workplace bullying on psychological distress. The study findings add solid and valuable contributions to concerned scholars and hoteliers by illustrating how bullying behavior could impact employees' psychological distress and their work engagement, considering the interaction role of self-compassion on the link between bullying behavior on employees' psychological distress. Limitations and future research are further discussed.
Keywords: Workplace bullying; Psychological distress; Work engagement; Self-compassion; Hotels